Boron nitride / epoxy resin heat-conducting composite material as well as preparation method and application thereof

The preparation of three-dimensional vertical orientation composite materials of modified boron nitride, nanocellulose, carbon nanotubes and borax by ice template method, solving the cost and processing complexity problems caused by high load fillers in the prior art, and achieving high thermal conductivity and Low resistivity effect.

CN119463414APending Publication Date: 2025-02-18TIANJIN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411337787.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When existing polymer-based thermal conductivity composites increase the thermal conductivity (TC), they usually require high load fillers, resulting in high material cost, large weight, complex processing performance, and high energy consumption, high cost and output of BN peeling process. Low.

Method used

The three-dimensional vertical orientation composite material was prepared by ice template method, and the lignin sulfonate modified boron nitride, carboxymethyl nanocellulose, carboxylated carbon nanotubes and borax were used as raw materials to form a thermally conductive composite material, which was used as epoxy resin. New enhanced thermal and electrical insulating fillers.

Benefits of technology

It significantly improves the in-plane thermal conductivity (TC) of the composite material to 1.459W/(m·K) and has a resistivity higher than 108Ω·㎝, which meets the insulation requirements and achieves high thermal conductivity under low filler loads, reducing costs and processing complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463414A_ABST
    Figure CN119463414A_ABST
Patent Text Reader

Abstract

The invention provides a boron nitride / epoxy resin heat-conducting composite material as well as a preparation method and application thereof. The boron nitride / epoxy resin heat-conducting composite material comprises the following raw material components: lignosulfonate; boron nitride; deionized water; a carboxymethyl nano cellulose solution; carboxylating the carbon nanotubes; borax; an epoxy resin; 1, 1, 2-cyclohexanedicarboxylic anhydride; the catalyst is 2, 2, 4, 6-tri (dimethylaminomethyl) phenol. The invention relates to a preparation method and application of a novel h-BN (boron nitride) composite material for thermal management, in particular to a three-dimensional vertical orientation composite material prepared by using lignosulfonate (LS) modified h-BN, cellulose nanofibers (C-CNF), carboxymethyl carbon nanotubes (C-CNT) and borax (B) as raw materials and adopting an ice template method. And the filler can be used as a novel enhanced heat conduction and electrical insulation filler in epoxy resin. According to the invention, BN is firstly modified, and surface modification is carried out on BN through sodium lignin sulfonate, so that compared with direct use of unmodified BN, the problem of poor compatibility and dispersibility of BN in the composite material is solved, and the heat-conducting property of the composite material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer-based thermally conductive composite materials, and in particular to a boron nitride / epoxy resin thermally conductive composite material and a preparation method and application thereof. Background Art

[0002] Efficient thermal management materials are crucial to the operating efficiency, long-term reliability and service life of electronic devices. In recent years, with the rapid development of communication technology and electronic devices, electronic devices have developed to a stage of high integration, high power and miniaturization. In particular, the rapid development of the fifth generation of communication technology (5G) has put forward higher requirements for thermal conductive materials. Therefore, efficient thermal management materials are urgently needed to ensure the long-term use and stable operation of devices. In recent years, in view of the excellent comprehensive properties of polymer-based materials, the application of these materials in thermal management systems has attracted widespread attention. However, the low intrinsic thermal conductivity (TC) of the polymer matrix greatly limits its practical application. At present, adding thermally conductive fillers directly to the polymer matrix is ​​the most common method for preparing polymer-based thermally conductive composites. Generally, in order to achieve a satisfactory TC, a high loading of fillers is usually required. High loading may help to improve the thermal conductivity of the composite material, but it inevitably leads to high cost, heavy weight and complex processing performance of the composite material, which is not conducive to its practical application. Therefore, it is extremely necessary to achieve high TC of the composite material while maintaining a low filler load.

[0003] It has been shown that introducing fillers into interconnected 3D thermally conductive frameworks as thermally enhanced phases into polymer matrices is an effective strategy. Boron nitride, known as "white graphite", has the advantages of high thermal conductivity, wide bandgap, excellent chemical stability, high aspect ratio morphology, and excellent electrical insulation, and has been widely used to prepare thermally conductive composites. To date, 3D networks based on BN have been prepared by a variety of strategies, such as layer-by-layer assembly, chemical vapor deposition, and electrospinning technology. Although these methods have made some progress in enhancing TC, most of these methods involve the step of exfoliating bulk BN into boron nitride nanosheets. However, due to high energy consumption, high cost, time consumption, and low yield, the exfoliation of BN has only reached laboratory scale. In recent years, the ice template method has attracted widespread attention due to its ability to directly use bulk BN (without exfoliation) as a filler to construct 3D BN networks. However, there are still some gaps between BN sheets in 3D scaffolds, especially when a small amount of BN is filled in the polymer matrix. Due to the large thermal resistance in the polymer-filler and filler-filler interfaces, the needs of practical applications cannot be met, and the advantages of BN have not been fully utilized.

[0004] Lignosulfonate (LS), isolated from byproducts of pulping and biorefining industries, is one of the most abundant biopolymers, with an annual global production of 9.8 × 105 Tons. The valorization of LS is challenging because it retains some of its own natural recalcitrance. Chemically, LS consists of a hydrophobic hyperbranched macromolecular backbone and abundant hydrophilic end groups (such as sulfonic acid groups), which makes LS highly water-soluble and may facilitate dispersion. At the same time, it still has the basic three-dimensional structure of the raw material lignin, which can physically hinder aggregation and immobilize it.

[0005] After searching, several patent documents related to this patent application were found, specifically:

[0006] The Chinese patent with publication number CN114456417B provides a preparation and application of green and degradable electronic device substrate materials. The present invention selects nanocellulose CNF and modified and graded lignin FE-LS to prepare green electronic substrates. Through the pretreatment of dialysis fraction and epoxidation modification, the heterogeneous structure and moderate surface activity of lignin are significantly improved.

[0007] The Chinese patent with publication number CN117858385B provides a multilayer PCB board and a preparation method thereof. 3-chlorosulfonylbenzoyl chloride and 4,4-diaminodiphenyl ether are used as raw materials to synthesize polyamide sulfonamide, which is epoxidized and then grafted with amination boron nitride to prepare a modified epoxy resin as a base material for a thermally conductive adhesive. Boron nitride and carbon nanotubes are introduced into the thermally conductive adhesive as thermally conductive fillers and toughening agents, and the boron nitride and carbon nanotubes are modified, wherein the carbon nanotubes are acidified to prepare carboxylated carbon nanotubes, which are then composited with amination boron nitride to form a three-dimensional composite thermally conductive filler with a thermally conductive channel structure. In order to prevent the composite thermally conductive filler from falling off from the thermally conductive adhesive and improve the flame retardancy of the copper clad laminate, triethylamine is used as an acid binding agent and catalyst, phosphorus oxychloride and 4,4-diaminodiphenylmethane are used as reaction monomers, and in-situ polymerization is carried out on the surface of the composite thermally conductive filler to obtain a branched composite thermally conductive filler.

[0008] The Chinese patent with publication number CN116694024A provides a boron nitride-silver / epoxy resin thermal conductive composite material and its preparation method. The preparation method comprises the following steps: first, prepare a boron nitride-silver composite filler; then, mix and stir the boron nitride-silver composite filler, a binder, a pore-forming material and a solvent to obtain a first mixture; then, inject the first mixture into a mold, remove the solvent first, then remove the pore-forming material, and obtain a three-dimensional boron nitride-silver thermal conductive skeleton; then mix the epoxy resin, a diluent and a curing agent to obtain a resin mixture; finally, mix the three-dimensional boron nitride-silver thermal conductive skeleton and the resin mixture, and then perform vacuum degassing and thermal curing treatment in sequence to obtain a boron nitride-silver / epoxy resin thermal conductive composite material.

[0009] A Chinese patent with publication number CN115819923A provides a high thermal conductivity and high insulation epoxy resin composite material and a preparation method thereof, the method comprising: (1) mixing an aqueous binder solution, an aqueous foaming agent solution and water to obtain a mixed solution; (2) mixing an inorganic thermal conductive filler and the mixed solution, and then stirring; (3) freezing the foaming liquid and then drying it; (4) mixing an epoxy resin, a curing agent and an accelerator, and then evacuating the mixture; (5) placing a thermally conductive skeleton in an uncured epoxy resin solution for vacuum degassing, and then heating and curing, so as to obtain a high thermal conductivity and high insulation epoxy resin composite material.

[0010] After comparative analysis, this patent application adopts the ice template method to prepare three-dimensional vertically oriented composite materials, and the preparation process or the main technical problems solved are different from those of the above-mentioned patent documents. Summary of the invention

[0011] The invention provides a boron nitride / epoxy resin thermal conductive composite material and a preparation method and application thereof. Boron nitride (BN) modified with lignin sulfonate (LS) and carboxymethyl nanocellulose (C-CNF), carboxymethyl carbon nanotubes (C-CNT) and borax (B) are used as raw materials, and a three-dimensional vertically oriented composite material is prepared by an ice template method, which can be used as a new type of enhanced thermal conductivity and electrical insulation filler in epoxy resin. Compared with pure epoxy resin (EP), the prepared composite material (B-3D-LS-BN-CNT / EP) can significantly improve its in-plane thermal conductivity (TC) due to its long vertically oriented skeleton as a thermal conduction path. In addition, a small amount of added carbon nanotubes are separated by insulating BN, resulting in electrical insulation of the entire skeleton. BN modified by LS can be dispersed and react with C-CNT and C-CNF through hydrogen bonds. The borate introduced by borax (B) can promote the mutual bonding between the components, realize interface regulation and multifunctional integration.

[0012] A boron nitride / epoxy resin thermal conductive composite material, comprising the following raw material components:

[0013] lignin sulfonates;

[0014] Boron nitride;

[0015] Deionized water;

[0016] Carboxymethyl nanocellulose solution;

[0017] Carboxylated carbon nanotubes;

[0018] Borax;

[0019] Epoxy resin;

[0020] 1,2-cyclohexanedicarboxylic anhydride;

[0021] 2,4,6-Tris(dimethylaminomethyl)phenol.

[0022] The steps of the preparation method of the above-mentioned boron nitride / epoxy resin thermal conductive composite material are as follows:

[0023] (1) dispersing carbon nanotubes in a H2SO4 / HNO3 mixed acid solution and stirring continuously for 3 h for chemical oxidation;

[0024] (2) diluting the obtained suspension with deionized water and washing repeatedly until it becomes neutral;

[0025] (3) freeze-drying the oxidized carbon nanotubes for 48 hours to obtain carboxylated carbon nanotubes;

[0026] (4) adding deionized water to the mixture of lignin sulfonate and boron nitride, stirring evenly and ultrasonicating for 2 h to obtain BN-LS slurry;

[0027] (5) Add carboxylated carbon nanotubes to the BN-LS slurry, add carboxymethyl nanocellulose solution and borax, stir evenly and then ultrasonicate for 2 h;

[0028] (6) The slurry after ultrasonic treatment was stirred and poured into a Teflon tube with an inner diameter of 30 mm and a copper plate at the bottom, the tube was placed on the copper plate, and then the copper plate was cooled with liquid nitrogen;

[0029] (7) freeze-drying the frozen sample to obtain a B-LS-BN-CNT thermal conductive skeleton;

[0030] (8) mixing and stirring epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol to form a uniform mixture;

[0031] (9) completely immersing the prepared B-LS-BN-CNT skeleton into the mixture obtained in step (8), and vacuum-injecting in a vacuum oven;

[0032] (10) After curing in an oven, 3D BN / Epoxy composite materials were obtained.

[0033] Moreover, in step (1), the ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1, and the stirring temperature is 60°C.

[0034] Moreover, in step (2), the mass ratio of boron nitride to deionized water is 1:2-3.

[0035] Moreover, in steps (3) and (7), the freeze-drying temperature is -55°C and the pressure is less than 20Pa.

[0036] Moreover, in step (4), the mass ratio of boron nitride to sodium lignin sulfonate is 10:1.

[0037] Moreover, in step (5), the mass ratio of the carboxymethyl carbon nanotubes to the boron nitride added in step (4) is 1:29-30, the ratio of the carboxymethyl nanocellulose solution to the boron nitride added in step (4) is 5:2-3 (ml / g, v / w), and the mass ratio of the carboxymethyl carbon nanotubes to borax is 1:1.

[0038] Moreover, in step (8), the mass ratio of the epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100:80:0.6.

[0039] Moreover, in step (9), the vacuum oven temperature is 60°C.

[0040] Moreover, in step (10), the curing conditions are curing at 90° C. for 2 h and post-treatment at 120° C. for 4 h.

[0041] A thermally conductive filler adopts the boron nitride / epoxy resin thermally conductive composite material as a thermally conductive material.

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] (1) The present invention first modifies BN and performs surface modification on BN by sodium lignin sulfonate. Compared with directly using unmodified BN, the present invention solves the problem of poor compatibility and dispersibility of BN in the composite material, thereby further improving the thermal conductivity of the composite material.

[0044] (2) The present invention uses borax as a cross-linking agent. The borate ions introduced by borax can promote the mutual bonding between the components, thereby achieving interface regulation and multifunctional integration.

[0045] (3) The thermal conductivity of the composite material of the present invention is as high as 1.459 W / (m·K) at a low filling amount of 15% thermal conductive filler, and the resistivity is higher than 10 8 Ω·㎝, meeting insulation requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 : Flow chart for preparing the thermally conductive composite material provided by the present invention.

[0047] Figure 2 : SEM images of the thermally conductive skeleton and thermally conductive composite material prepared, wherein:

[0048] (a) LS-BN skeleton;

[0049] (b) LS-BN-CNT skeleton;

[0050] (c) B-LS-BN-CNT skeleton;

[0051] (d) B-LS-BN-CNT / EP skeleton.

[0052] Figure 3 (a) is a schematic diagram of the thermal conductivity of the composite material provided by the present invention;

[0053] Figure 3 (b) is the composite material interface interaction structure model provided by the present invention;

[0054] Figure 3 (c) is a schematic diagram model of the composite material insulation provided by the present invention.

[0055] Figure 4 (a) From left to right are infrared thermal images of the composite materials of BN / EP (Comparative Example 1), LS-BN / EP (Comparative Example 2), LS-BN-CNT / EP (Comparative Example 3) and B-LS-BN-CNT / EP (Example 1) at different heating times;

[0056] Figure 4 (b) The surface temperature of the composite material provided by the present invention changes with heating time;

[0057] Figure 4 (c) is a graph showing the change in surface temperature of the composite material provided by the present invention with cooling time. DETAILED DESCRIPTION

[0058] The present invention will be further described in detail through specific embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0059] It should be noted that, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0060] Example 1

[0061] A vertically oriented carbon nanotube / boron nitride / cellulose framework with borax as a crosslinking agent is used for an efficient thermal conductive epoxy composite material with electrical insulation and a preparation method thereof, the steps are as follows:

[0062] (1) 1 g of original carbon nanotubes was dispersed in 40 ml of H2SO4 / HNO3 mixed acid solution, wherein the volume ratio of H2SO4 to HNO3 was 3:1, and the solution was continuously stirred in a 60°C water bath for 3 h for chemical oxidation. After the reaction was completed, the obtained suspension was diluted with deionized water and repeatedly washed until it became neutral, and the oxidized carbon nanotubes were freeze-dried for 48 hours to obtain carboxylated carbon nanotubes;

[0063] (2) Add 2.09 g BN and 0.209 sodium lignin sulfonate to 5 ml deionized water, stir well and sonicate for 2 h;

[0064] (3) Add 0.07 g of carboxylated carbon nanotubes to the LS-BN slurry, add 5 ml of carboxymethyl nanocellulose solution and 0.07 g of borax, stir evenly and then ultrasonicate for 2 h;

[0065] (4) The slurry after ultrasonic treatment was stirred and poured into a Teflon tube with an inner diameter of 30 mm and a copper plate at the bottom, and the tube was placed on the copper plate. The copper plate was then cooled with liquid nitrogen, and the frozen sample was freeze-dried to obtain a 3D BN thermal conductive skeleton.

[0066] (5) firstly, epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are mixed and stirred to form a uniform mixture, wherein the mass ratio of epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100:80:0.6;

[0067] (6) The prepared BN skeleton was completely immersed in the mixture and further vacuum injected in a vacuum oven and cured in the oven to obtain the B-LS-BN-CNT / EP composite material. The curing conditions were 90 °C for 2 h and 120 °C for 4 h.

[0068] Comparative Example 1

[0069] (1) Add 2.09 g BN to 5 ml carboxymethyl nanocellulose solution and 5 ml deionized water, stir evenly and then ultrasonicate for 2 h;

[0070] (2) Pour the stirred slurry into a Teflon tube with an inner diameter of 30 mm and a copper plate at the bottom, place the tube on the copper plate, cool the copper plate with liquid nitrogen, and freeze-dry the frozen sample to obtain a BN thermal conductive skeleton;

[0071] (3) firstly, epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are mixed and stirred to form a uniform mixture, wherein the mass ratio of epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100:80:0.6;

[0072] (4) The prepared BN skeleton was completely immersed in the mixture and further vacuum injected in a vacuum oven and cured in the oven to obtain a BN / EP composite material. The curing conditions were 90 °C for 2 h and 120 °C for 4 h.

[0073] Comparative Example 2

[0074] (1) Add 2.09 g BN and 0.209 sodium lignin sulfonate to 5 ml deionized water, stir well and sonicate for 2 h;

[0075] (2) Add 5 ml of carboxymethyl nanocellulose solution to the LS-BN slurry, stir evenly, and then ultrasonicate for 2 h;

[0076] (2) Pour the stirred slurry into a Teflon tube with an inner diameter of 30 mm and a copper plate at the bottom, place the tube on the copper plate, cool the copper plate with liquid nitrogen, and freeze-dry the frozen sample to obtain a LS-BN thermal conductive skeleton;

[0077] (3) firstly, epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are mixed and stirred to form a uniform mixture, wherein the mass ratio of epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100:80:0.6;

[0078] (4) The prepared LS-BN skeleton was completely immersed in the mixture and further vacuum injected in a vacuum oven and cured in the oven to obtain the LS-BN / EP composite material. The curing conditions were 90 °C for 2 h and 120 °C for 4 h.

[0079] Comparative Example 3

[0080] (1) 1 g of original carbon nanotubes was dispersed in 40 ml of H2SO4 / HNO3 mixed acid solution, wherein the volume ratio of H2SO4 to HNO3 was 3:1, and the solution was continuously stirred in a 60°C water bath for 3 h for chemical oxidation. After the reaction was completed, the obtained suspension was diluted with deionized water and repeatedly washed until it became neutral, and the oxidized carbon nanotubes were freeze-dried for 48 hours to obtain carboxylated carbon nanotubes;

[0081] (2) Add 2.09 g BN and 0.209 sodium lignin sulfonate mixture into 5 ml deionized water, stir evenly and sonicate for 2 h;

[0082] (3) Add 0.07 g of carboxylated carbon nanotubes to the LS-BN slurry and add 5 ml of carboxymethyl nanocellulose solution, stir evenly and then ultrasonicate for 2 h;

[0083] (4) stirring the slurry after ultrasonic treatment and pouring it into a Teflon tube with an inner diameter of 30 mm and a copper plate at the bottom, placing the tube on the copper plate, then cooling the copper plate with liquid nitrogen, and freeze-drying the frozen sample to obtain a LS-B-CNT thermal conductive skeleton;

[0084] (5) firstly, epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are mixed and stirred to form a uniform mixture, wherein the mass ratio of epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100:80:0.6;

[0085] (6) The prepared LS-BN-CNT skeleton was completely immersed in the mixture and further vacuum injected in a vacuum oven and cured in the oven to obtain the LS-BN-CNT / EP composite material. The curing conditions were 90 °C for 2 h and 120 °C for 4 h.

[0086] Comparative analysis: Compared with pure EP, the prepared composite material (B-LS-BN-CNT / EP) can significantly improve its in-plane thermal conductivity (TC) due to its long vertically oriented skeleton as a thermal conduction path. In addition, the small amount of carbon nanotubes added are separated by insulating BN, resulting in electrical insulation of the entire skeleton. LS-modified BN can be dispersed in water and combined with C-CNT and C-CNF through hydrogen bonds. The borate introduced by borax (B) can promote the mutual bonding between the components, realize interface regulation and multifunctional integration. When the filler loading is 15wt%, the thermal conductivity of the prepared composite material (B-LS-BN-CNT / EP) is as high as 1.459W / (m·K), which is higher than the thermal conductivity of the comparative examples BN / EP (0.632W / (m·K)), LS-BN / EP (1.214W / (m·K)) and LS-BN-CNT / EP (1.341W / (m·K)). The invention is green and environmentally friendly, has a simple preparation method, and the thermally conductive composite material can still have high thermal conductivity and heat dissipation performance under the condition of low BN filling, and has the characteristics of low cost and excellent performance.

[0087] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A boron nitride / epoxy resin thermal conductive composite material, characterized in that: The invention comprises the following raw material components: lignin sulfonate; boron nitride; deionized water; carboxymethyl nanocellulose solution; carboxylated carbon nanotubes; borax; epoxy resin; 1,2-cyclohexanedicarboxylic anhydride; and 2,4,6-tris(dimethylaminomethyl)phenol.

2. A method for preparing the boron nitride / epoxy resin thermal conductive composite material as claimed in claim 1, characterized in that: The steps are as follows: (1) dispersing carbon nanotubes in a H2SO4 / HNO3 mixed acid solution and stirring continuously for 3 h for chemical oxidation; (2) diluting the obtained suspension with deionized water and washing repeatedly until it becomes neutral; (3) freeze-drying the oxidized carbon nanotubes for 48 hours to obtain carboxylated carbon nanotubes; (4) adding deionized water to the mixture of lignin sulfonate and boron nitride, stirring evenly and ultrasonicating for 2 h to obtain BN-LS slurry; (5) Add carboxylated carbon nanotubes to the BN-LS slurry, add carboxymethyl nanocellulose solution and borax, stir evenly and then ultrasonicate for 2 h; (6) The slurry after ultrasonic treatment was stirred and poured into a Teflon tube with an inner diameter of 30 mm and a copper plate at the bottom, the tube was placed on the copper plate, and then the copper plate was cooled with liquid nitrogen; (7) freeze-drying the frozen sample to obtain a B-LS-BN-CNT thermal conductive skeleton; (8) mixing and stirring epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol to form a uniform mixture; (9) completely immersing the prepared B-LS-BN-CNT skeleton into the mixture obtained in step (8), and vacuum-injecting in a vacuum oven; (10) After curing in an oven, 3D BN / Epoxy composite materials were obtained.

3. The method for preparing the boron nitride / epoxy resin thermally conductive composite material according to claim 2, characterized in that: In step (1), the ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1, and the stirring temperature is 60°C.

4. The method for preparing the boron nitride / epoxy resin thermally conductive composite material according to claim 2, characterized in that: In step (2), the mass ratio of boron nitride to deionized water is 1:2-3.

5. The method for preparing the boron nitride / epoxy resin thermally conductive composite material according to claim 2, characterized in that: In steps (3) and (7), the freeze-drying temperature is -55°C and the pressure is less than 20Pa.

6. The method for preparing the boron nitride / epoxy resin thermally conductive composite material according to claim 2, characterized in that: In step (4), the mass ratio of boron nitride to sodium lignin sulfonate is 10:

1.

7. The method for preparing the boron nitride / epoxy resin thermally conductive composite material according to claim 2, characterized in that: In step (5), the mass ratio of the carboxymethyl carbon nanotubes to the boron nitride added in step (4) is 1:29-30, the ratio of the carboxymethyl nanocellulose solution to the boron nitride added in step (4) is 5:2-3 (ml / g, v / w), and the mass ratio of the carboxymethyl carbon nanotubes to borax is 1:

1.

8. The method for preparing the boron nitride / epoxy resin thermally conductive composite material according to claim 2, characterized in that: In step (8), the mass ratio of the epoxy resin, 1,2-cyclohexanedicarboxylic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol is 100:80:0.

6.

9. The method for preparing the boron nitride / epoxy resin thermally conductive composite material according to claim 2, characterized in that: In step (9), the vacuum oven temperature is 60° C., and in step (10), the curing conditions are curing at 90° C. for 2 h and post-treatment at 120° C. for 4 h.

10. A thermally conductive filler, characterized in that: The boron nitride / epoxy resin thermally conductive composite material prepared by the preparation method of any one of claims 2 to 9 is used as a thermally conductive material.

Citation Information

Patent Citations

  • Preparation and application of a bioplastic substrate material for green electronic devices

    CN114456417B

  • High-thermal-conductivity and high-insulation epoxy resin composite material and preparation method thereof

    CN115819923A

  • Boron nitride-silver / epoxy resin heat-conducting composite material and preparation method thereof

    CN116694024A

  • A multi-layer PCB board and preparation method thereof

    CN117858385B

Cited By

  • Recyclable high-barrier packaging film and preparation method thereof

    CN119682346A

  • A recyclable high barrier packaging film and preparation method thereof

    CN119682346B

  • High-thermal-conductivity insulating elastic composite film for high-power module of new energy automobile and preparation method of high-thermal-conductivity insulating elastic composite film

    CN122445173A